2022
DOI: 10.1038/s41467-022-29143-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies of metabolites in Finnish men identify disease-relevant loci

Abstract: Few studies have explored the impact of rare variants (minor allele frequency < 1%) on highly heritable plasma metabolites identified in metabolomic screens. The Finnish population provides an ideal opportunity for such explorations, given the multiple bottlenecks and expansions that have shaped its history, and the enrichment for many otherwise rare alleles that has resulted. Here, we report genetic associations for 1391 plasma metabolites in 6136 men from the late-settlement region of Finland. We identify… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 105 publications
(149 citation statements)
references
References 86 publications
5
116
0
Order By: Relevance
“…Even though previous metabolite GWAS have benefited from a larger sample size or more metabolites tested, our study queries the entire coding space, which, due to the high cost of sequencing is infeasible for many mGWAS studies, who often use imputed genotype data [ 5 , 6 , 7 , 8 ]. Despite the smaller size of our panel compared to others, the Biocrates kit used here measures some metabolites missed by other common platforms, such as Metabolon [ 5 , 6 , 8 , 29 , 30 ] or Nightingale [ 6 , 11 ]. For example, Nightingale does not measure the amino acids tryptophan, arginine, or aspartate, and neither Metabolon nor Nightingale measures the biogenic amines histamine, spermine, or putrescine, or the acylcarnitines decadienylcarnitine or dodecanedioylcarnitine.…”
Section: Discussionmentioning
confidence: 99%
“…Even though previous metabolite GWAS have benefited from a larger sample size or more metabolites tested, our study queries the entire coding space, which, due to the high cost of sequencing is infeasible for many mGWAS studies, who often use imputed genotype data [ 5 , 6 , 7 , 8 ]. Despite the smaller size of our panel compared to others, the Biocrates kit used here measures some metabolites missed by other common platforms, such as Metabolon [ 5 , 6 , 8 , 29 , 30 ] or Nightingale [ 6 , 11 ]. For example, Nightingale does not measure the amino acids tryptophan, arginine, or aspartate, and neither Metabolon nor Nightingale measures the biogenic amines histamine, spermine, or putrescine, or the acylcarnitines decadienylcarnitine or dodecanedioylcarnitine.…”
Section: Discussionmentioning
confidence: 99%
“…Its limitation lies in that transcript abundance is unlikely to be the most relevant molecular phenotype in revealing gene-trait relationships for all scenarios. Many authors have shown that isoform usage [47, 48, 49, 50], RNA degradation [51, 52, 53], protein abundance [54, 55, 56], and many other molecular traits [21, 57, 58] play critical roles in the etiology of different diseases. This point is also evidenced by our analyses in which eQTL data only explain a fraction of significant GWAS loci in both Sinnott-Armstrong et al .…”
Section: Discussionmentioning
confidence: 99%
“…Its limitation lies in that transcript abundance is unlikely to be the most relevant molecular phenotype in revealing gene-trait relationships for all scenarios. Many authors have shown that isoform usage [47,48,49,50], RNA degradation [51,52,53], protein abundance [54,55,56], and many other molecular traits [21,57,58] We illustrate that with proper probabilistic quantification of evidence, rigorous gene set enrichment analysis can be performed by applying INTACT-GSE. We note that utilizing the estimated enrichment parameters and gene set information can further boost the discovery of putative causal genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-targeted metabolomics profiling was performed at Metabolon, Inc. (Morrisville, NC, USA) on EDTA plasma samples obtained after an overnight fast from 8679 participants, as previously described in detail [ 51 , 52 , 53 ]. The Metabolon DiscoveryHD4 platform was applied to assay named metabolites.…”
Section: Methodsmentioning
confidence: 99%